The Costs of Supervisory Fragmentation in Europe - Martin Schüler; Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Financial markets in Europe become more and more integrated. The persisting fragmentation of financial supervision, however, constitutes a lasting obstacle to integration. The aim of this paper is to assess these costs of supervisory fragmentation. We find clear evidence for the existence of economies of scale in banking supervision. An increase in supervisory output by one percent causes institutional supervisory cost to rise by only some 0.5 percent. Based on these estimation results we predict institutional cost saving of around 15 percent in a plausible simulation scenario representing a cost-efficient European supervisory framework.
Keywords: G28; 330; financial supervision; costs; economies of scale; Internationaler Finanzmarkt; Marktintegration; Bankenaufsicht; Soziale Kosten; Europa